The construction of teaching professionality - Oliveira de Azevedo, Heloisa Helena (2013)
This article was prepared by the results of a research of a investigation about the formative strategies developed by educators related to the construction of the professionality of future childhood and elementary school teachers.From the analysis of the content of the interviews, we want to know what the educators think about the teaching profession and conducting training activities aimed at building the professionalism of future teachers.With theoretical bases for analyses related to the historical-critical conception of education, we inferred that educators have tried to break with the traditional paradigm of teacher’s education, creating new learning alternatives and stimulating the construction of a new professionality that overcomes the culture of isolated an individual thinking